DUKUNGAN KELUARGA DAN RESILIENSI DIRI TERHADAP PENYESUAIAN SOSIAL PADA PENYANDANG TUNA NETRA - Marida, Lisna; Ekasari, Agustina (Program Studi Psikologi, Fakultas Ilmu Sosial dan Ilmu Politik Universitas Islam 45 Bekasi, 2017)
Physical limitations force one to continue living with all the limitations it has, just as the blind person is often depicted with a deficient figure. Disabilities that make people feel inferior, embarrassed, useless, and not confident in socializing with the environment. This study aims to determine the relationship between family support and self-resilience to social adjustment. The subject of this research is the blind person in